Effect of metal ions on the anti-corrosion properties of γ-glycidoxypropyltrimethoxysilane coatings on cold-rolled iron. Issue 2 (7th March 2016) - Ge, Shengsong; Li, Menglong; Shao, Qian; Liu, Ke; Wang, Junxiang; Yi, Fengjiao
Abstract : Purpose: – This paper aims to clarify the effect of metal ions added in the γ-glycidoxypropyltrimethoxysilane (γ-GPS) solutions on the anti-corrosion properties of the γ-GPS coatings on cold-rolled iron (CRI). Design/methodology/approach: – The transformations of functional groups involved in reactions during the coating process were characterized by Fourier transformed infrared spectroscopy (FTIR), and the thickness of the γ-GPS coatings on the CRI substrates was measured using high-powered microscopy. The anti-corrosion properties of γ-GPS-treated samples were evaluated by neutral salt spray tests, polarization curves and electrochemical impedance spectroscopy measurements. Findings: – The results show that Zn2+ and Mg2+ in the γ-GPS solutions promote the formation of Si-O-Si and Si-O-Fe bonds and improve the anti-corrosion properties of the γ-GPS coatings on CRI. However, Al3+ and Na+ in the γ-GPS solutions do not play this role. Originality/value: – Although there have been previous research studies on the γ-GPS coatings on CRI, this paper is the first to study the effect of metal ions added in the silane solutions on the anti-corrosion properties of the γ-GPS coatings, and it has been confirmed that the anti-corrosion properties changed when Zn2+ (or Mg2+) is present.